618 Building the conversation for hospital-based injury prevention program capacity in texas, USA. (1st September 2016) - Contreras, Mary Ann; Edwards, Courtney; Stephens-Stidham, Shelli; Williams, Stewart
Abstract : Background: Trauma centres in the U.S. seeking verification by the American College of Surgeons must meet certain criteria outlined in 2014 Resources for Optimal Care of the Injured Patient . The criteria state that trauma centres have an "organised and effective approach to injury prevention." Description of the problem: There are well-defined guidelines for state and local public health injury programs; however, guidance for hospital-based programs has been general and left to individual interpretation. Several U.S. trauma/injury prevention associations and organisations have expressed an interest in developing stronger guidelines for hospital-based injury prevention programs. In 2014, the Texas Governor's EMS and Trauma Advisory Council (GETAC) Injury Prevention Committee convened a work group of Texas representatives from trauma-related associations to reach consensus on standard hospital-based injury prevention program core components for Texas hospitals. Results: Standardised components were developed with input from representatives of the invited Texas organisations, including representatives from all levels of trauma designation (I–IV). Resource documents from U.S. organisations were utilised. The components were developed to be applicable to all hospital-based injury programs regardless of staffing levels or capacity. A document, Hospital-Based Injury Prevention Components, was developed to explain and provide supporting materials for each identified core component. The document was endorsed by GETAC in November 2014 and disseminated to Texas hospital trauma and injury prevention professionals in February 2015. No legislative rule changes or requirements were associated with the endorsement. A survey link to assess use of the document was disseminated in August 2015. Conclusions: Results of the survey will be utilised to determine adoption of the document and inform future improvements and dissemination in Texas. Additionally, the Texas process has generated national attention and may be used to develop national standardised guidelines.